2019
DOI: 10.1038/s41467-019-09749-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-translational assembly of mammalian nuclear multisubunit complexes

Abstract: Cells dedicate significant energy to build proteins often organized in multiprotein assemblies with tightly regulated stoichiometries. As genes encoding subunits assembling in a multisubunit complex are dispersed in the genome of eukaryotes, it is unclear how these protein complexes assemble. Here, we show that mammalian nuclear transcription complexes (TFIID, TREX-2 and SAGA) composed of a large number of subunits, but lacking precise architectural details are built co-translationally. We demonstrate that dim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
147
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(177 citation statements)
references
References 55 publications
14
147
2
4
Order By: Relevance
“…Indeed some proteins are by themselves toxic to the cell [112] or unstable, intrinsically disordered and prone to aggregation [2,113]. Recent studies suggest that several mammalian nuclear transcription complexes assemble cotranslationally [114]. A systematic study of eukaryotic subunit assembly during translation by selective ribosome profiling shows that out of 12 hetero-oligomeric complexes studied, nine assembled cotranslationally and the remainder assembled with chaperone assistance [26].…”
Section: Cotranslational Subunits Assemblymentioning
confidence: 99%
“…Indeed some proteins are by themselves toxic to the cell [112] or unstable, intrinsically disordered and prone to aggregation [2,113]. Recent studies suggest that several mammalian nuclear transcription complexes assemble cotranslationally [114]. A systematic study of eukaryotic subunit assembly during translation by selective ribosome profiling shows that out of 12 hetero-oligomeric complexes studied, nine assembled cotranslationally and the remainder assembled with chaperone assistance [26].…”
Section: Cotranslational Subunits Assemblymentioning
confidence: 99%
“…Our data also suggests that triggering iSRC by mild proteostasis stress may offer an opportunity to ameliorate OxPhos-deficiency in mitochondrial diseases. On the other hand, many protein complexes assemble co-translationally to prevent aggregation of free subunits (Kamenova et al, 2019;Shiber et al, 2018). Nuclear-encoded RC-subunits do not enjoy that opportunity as these are imported from cytoplasm before their assembly inside mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that unassembled proteins are prone to degradation through exposure of degrons that are normally shielded when in complex [64]. Alternatively, studies in bacteria, yeast and mammalian cells suggest many multi-subunit complexes are built during translation, where proteins undergoing translation already begin interacting with their partners [65][66][67]. Preventing cotranslational binding and folding often results in degradation of the translating partners, suggesting a competition between protein folding and complex formation with degradation.…”
Section: Discussionmentioning
confidence: 99%